Improving Learner-Driven Teaching Practices through Reflective Assessment - Regan, Matthew T.; Young, Scott W. H.; Mannheimer, Sara (Evidence Based Library and Information Practice, 2020)
Objective – Reflective assessment is an effective method of teacher evaluation, serving as an approach for assessing teaching practices, generating insights, and connecting with colleagues, ultimately supporting meaningful transformation of teaching practice. In this paper, three librarians model a reflective assessment approach in evaluating and improving their experiences implementing learner-driven teaching practices in credit-bearing courses in topics related to library and information studies.Methods – Following a model of reflective assessment, we asked ourselves how our practice can better support learner-driven teaching practices, thus assessing and improving our own teaching and improving students’ learning experiences. Our process involved five steps: cohere around shared viewpoints, identify teaching practices for reflection, conduct reflection, discuss and analyze reflections to produce insights, and apply insights to improve teaching.Results – We reflect on five different learner-driven teaching practices: co-creative syllabus design, learner-defined personal learning goals, soliciting and responding to learner feedback, interdisciplinary discussions and exercises, and self-evaluation. We discuss improvements and refinements that we implemented in response to our reflective assessment, including more frequent checking in with students; more clarity regarding self-evaluation and grading; one-on-one meetings with all students; allowing students to negotiate, discuss, and determine assignment deadlines and dates; more flexibility with students’ work products; and increased pedagogical transparency. As a further result, our reflective process models an approachable framework for engaging in reflective assessment.Conclusion – This paper presents a model for reflective assessment of teaching in an academic library. We present a discussion of learner-driven teaching practices, and we offer a practical pathway for other teachers and practitioners to assess their teaching. We find that reflective assessment is an effective and insightful approach for understanding and improving learner-driven teaching practices.